Workplace Romance and Employee Engagement: A Mediated and Moderation Analysis - Noermijati, Noermijati; Kurniawati, Desi Tri; Hakim, Abdurrahman; Aurelia, Winny; Farhiya, Daniyatul; Masyhuri, Masyhuri (International Review of Management and Marketing, 2026)
This study examines the influence of workplace romance on employee engagement by incorporating deviant behavior and job stress as mediating variables and gender as a moderating factor. Drawing on Affective Events Theory, the study explains how interpersonal events in the workplace generate emotional and behavioral responses that influence employees’ engagement levels. A quantitative survey approach was employed, and data were collected from 210 employees working in private mining companies in Indonesia using a self-administered questionnaire. The data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) technique. The results indicate that workplace romance has a positive and significant effect on employee engagement. In addition, workplace romance significantly reduces deviant behavior and job stress, while both deviant behavior and job stress negatively affect employee engagement. The mediation analysis confirms that deviant behavior and job stress partially mediate the relationship between workplace romance and employee engagement. Furthermore, gender strengthens the relationship between workplace romance and employee engagement. These findings highlight the importance of managing interpersonal relationships in the workplace to enhance employee engagement while minimizing negative behavioral and psychological outcomes.